Program and status for the planned underground accelerator in the Dresden Felsenkeller. Issue 1 (January 2016) - Bemmerer, D; Akhmadaliev, S; Al-Abdullah, T; Anders, M; Cowan, T E; Elekes, Z; Junghans, A R; Gohl, St; Krause, J; Reinhardt, T P; Reinicke, S; Rimarzig, B; et al.
Abstract: The scientific program and curent status of the planned accelerator laboratory in the Felsenkeller shallow-underground facility in Dresden, Germany, are reviewed.